The effect of sediment resuspension on pelagic nitrogen fixation in a Danish fjord - Core incubations - Isabell Schlangen; Carolin Regina Löscher; Karl Michael Attard; Lisbeth Fürst Sørensen; Lasse Riemann (PANGAEA, 2025)
This dataset contains results from incubation experiments investigating the impact of sediment resuspension on nitrogen (N?) fixation in a microtidal fjord environment. Experiments were conducted seasonally during June, July, August, and September 2023 using water and sediment from Kærby Fed in Odense Fjord, Denmark. The aim was to evaluate whether varying intensities of resuspension affect pelagic N? fixation activity. Measured parameters include: (i) N? fixation rates, determined using the 15N? tracer method following Mohr et al. (2010), (ii) particulate organic carbon (POC) and particulate organic nitrogen (PON) content of the added sediment, analyzed by Elemental Analysis–Isotope Ratio Mass Spectrometry, (iii) concentrations of dissolved inorganic nitrogen (DIN) and phosphorus (DIP) in the overlying water, measured using a spectrophotometer. Incubations involved sediment slurries subjected to different resuspension intensities, simulating a range of bed-shear stress conditions. All treatments were conducted in triplicates, and the dataset includes standard deviations for replicate measurements. The data support assessments of how sediment-driven processes influence microbial nitrogen cycling in coastal zones of the Danish Baltic Sea.